Caracterización del recurso solar para evaluar el potencial energético en el campus matriz de la Universidad Técnica de Cotopaxi - Quinchiguango Ayala, Edgar German (2022)
This technological proposal makes a characterization of solar resource, focused on the knowing objective the energy potential that exists in Latacunga city, San Felipe neighborhood. To achieve his purpose, an instrument called a pyranometer was used for data acquiring and finding out solar radiation in the study area. Having a history of the information, subsequently quantitative and statistical analysis is proposed to describe and explain irradiance behavior as a function of time. Once this variable is analyzed, a conversion of units is generated used at calculation of solar energy to determine the amount of irradiation that exists in a day. At the end of the research, it was evidenced that at the study site there is an average irradiance of 452,31 W/m2 and an average irradiation of 5,4 kWh/m2 potential that can be harnessed in a given solar energy project.